Aerodynamic damping of inclined slender prisms. Issue 177 (June 2018) - Chen, Zeng-shun; Tse, K.T.; Kwok, K.C.S.; Kareem, Ahsan
Abstract: The aerodynamic damping of forward and backward inclined prisms has been identified through a series of forced vibration wind tunnel tests. The test results show that the amplitude of vibration and reduced wind velocity both have a significant effect on the aerodynamic damping of the inclined prisms, especially at reduced wind speeds where von Karman vortex lock-in occurs. The effect of forward and backward inclination on the characteristics of aerodynamic damping in inclined prisms is dissimilar to a vertical prism, and the characteristics have been discussed in terms of the unsteady aerodynamic force and Strouhal number in this study. This study not only advances our understanding on aerodynamic damping of inclined prisms, but also provides values that can be used to estimate aerodynamics and aeroelasticities of inclined prisms. Highlights: Forced vibration tests of inclined prisms performed. Aerodynamic damping of inclined prisms obtained. Characteristics of unsteady crosswind forces acting on inclined prisms discussed. The quasi-steady theory is not able to predict galloping instabilities of inclined prisms.